COMPARATIVE CURE AND SUPPRESSION EFFICACY OF FORMULATED GRANULES WITH A MARKETED SIMILAR PRODUCT - Ubieko, Edwin A.; Ubieko, Emmanuel A. (Universal Journal of Pharmaceutical Research, 2024)
Aim and Objectives: Malaria, a major global health challenge which makes antimalarial drugs one of the commonly prescribed class of drugs World-wide. The most vulnerable are the children and the women especially the expectant mothers. There is need to develop locally and readily available excipients from natural sources to replace imported ones currently being used by our local manufacturing industries. The purpose of the investigation was to test the formulated granules for oral suspension. Methods: Some weighed albino rats were infected with Plasmodium berghei, then the standard dose of the artemether-lumefantrine oral suspension formulated, a marketed product, and distilled water were administered ; 4/24 mg artemether-lumefantrine per kg body weight per oral to weighed albino rats. Then, other groups were administered standard dose of different formulated granules, a marketed similar product and distilled water respectively. These treated albino rats were then infected with Plasmodium berghei and blood samples were withdrawn from the tail veins, stained with Giemsa stain and the Plasmodium berghei count for the untreated and treated albino rats were determined. Results: The percentage clearance and suppression were calculated for the different formulations; pectin and its hybrid formulations, a marketed product and distilled water as a control which were 83.73, 85.2, 74.9 and 2.62, and 83.74, 85.2, 74.22, and 0% for curative and suppressive efficacies respectively. Conclusions: The investigations revealed that the most effective was the hybrid-formulated granules were closely followed by pectin-formulated granules and the least was the marketed product. Peer Review History: Received 17 May 2024; Reviewed 12 July 2024; Accepted 20 August; Available online 15 September 2024 Academic Editor: Dr. Asia Selman Abdullah , Pharmacy institute, University of Basrah, Iraq, asia_abdullah65@yahoo.com Reviewers: Ahmad Najib, Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id Dr. Ahmad Abdelsattar El-Ebiary, Tanta University Hospitals, Tanta, Egypt, a.ebiary@med.tanta.edu.eg